A dragon of black glass - Rollins, James, 1961- (Rollins, James, 1961- Moon fall, 2025)
"With the apocalyptic threat of moonfall looming ever closer, Nyxand her allies must venture into the eternally sunblasted lands to search for an ancient weapon buried untold millennia ago. All the while, enemies close upon her flanks, and a greater danger lurks ahead. For beneath a desert turned to glass, hidden from the scorching heat, life thrives--both wondrous and monstrous. But a more fearsome menace lies even deeper, where an ancient army has been seeded to protect a secret from any who dare seek it out. Yet, can Nyx truly trust those at her side? Or even herself? For while her gifts grow ever stronger, so does the danger of losing herself to a dark madness. Worst yet, the same afflicts Bashaliia, her winged and bonded brother"--